Understanding challenges, strategies, and the role of support networks in medication self-management among patients with type 2 diabetes: a qualitative study - Bernhard, Gerda; Ose, Dominik; Baudendistel, Ines; Seidling, Hanna; Stützle, Marion; Szecsenyi, Joachim; Wensing, Michel; Mahler, Cornelia (Diabetes educator, 2017)
PurposeThe purpose of this qualitative study was to investigate the challenges and strategies of patients with type 2 diabetes mellitus (T2DM) regarding daily management of their medication regimen focusing on the role of their support networks.MethodsA purposeful sample of 25 patients with T2DM was recruited from local self-help groups, general practitioner practices, and a university hospital in southwestern Germany. Four semi-structured focus groups were conducted to identify the challenges patients experienced, the strategies they used, and their collaboration with support networks to assist them in self-managing their medication regimen. Sessions were audio- and video-recorded, fully transcribed, and subjected to computer-aided qualitative content analysis, guided by the Self- and Family Management Framework (SFMF).ResultsPatients with T2DM experienced numerous challenges affecting medication self-management arising from their personal situation, health status and resources, characteristics of their regimen, and how health care is currently organized. Patients? self-initiated strategies included activating health care, community, social, and online resources; taking ownership of medication-related needs; and integrating medication-taking into daily life. Patients drew on self-help groups, family, and friends to discuss concerns regarding medication safety and receive experience-based information and advice for navigating within the health care system as well as practical hands-on support with daily medication self-management.ConclusionsUnderstanding the challenges and building on strategies patients with T2DM devised help diabetes educators to better address patients? needs and priorities and guide patient-centered interventions to support patients? self-management activities. Community and social support networks operating in patients? lives need to be engaged in the self-management support.